2017
DOI: 10.1007/s10735-017-9731-6
|View full text |Cite
|
Sign up to set email alerts
|

The expression of water channel proteins during human salivary gland development: a topographic study of aquaporins 1, 3 and 5

Abstract: a diffuse expression in mucous and serous acini, in addition to strong apical membrane expression within lumen of intercalated ductal cells. This topographic analysis of AQP1, 3 and 5 revealed differences in the expression pattern throughout salivary gland developmental stages, suggesting different roles for each protein in human glandular maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 42 publications
2
27
1
7
Order By: Relevance
“…In our study, AQP5 was expressed on the membranes of MEC mucous cells. In normal salivary glands, AQP5 was identified in acinar structures, as previously described [24,25,27,48]. In vitro evaluation also demonstrated the presence of AQP5 in MEC cells.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In our study, AQP5 was expressed on the membranes of MEC mucous cells. In normal salivary glands, AQP5 was identified in acinar structures, as previously described [24,25,27,48]. In vitro evaluation also demonstrated the presence of AQP5 in MEC cells.…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, studies of adult human glands demonstrated AQP1 in the myoepithelial cells that surround acini and intercalated ducts [25][26][27]. The presence of AQP1 in vascular endothelium and myoepithelial cells suggests that its expression may be important for water transport from the vascular lumen to the salivary gland, participating in the formation of the salivary fluid [24]. AQP1 is the only AQP expressed in myoepithelial cells [25][26][27].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations